Effect of Glucocorticoids on Serum Total Protein Level in control and experimental groups induced by Nephrotoxic Poison Concanavalin-A - Aqsa Mobeen, Amina Zulfiqar, Afia Jari, Amtul Hafeez, Haider Ali, Zain Imtiaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: According to international society of nephrology about 2 million people die with AKI every year. Elder patients and pediatrics have less immunity due to which concurrent administration of medication may damage the nephrons. Aim: To evaluate the effect of glucocorticoids on serum total protein level in control and experimental groups induced by nephrotoxic poison Concanavalin-A. Methodology: This experimental study was conducted at Agriculture University of Faisalabad-Pakistan following approval from ethical committee. Subject animals (n=12) were equally divided into 3 groups, 1st was control group, 2nd was treated group and 3rd was untreated group. The collected data was analyzed by using SPSS version 20. ANOVA ware applied with P-value< 0.05 Results: It was found that analysis of serum protein levels showed significant increase in total protein and globulin in Con-A induced toxic group as compare to control group. Conclusion: It was concluded that dexamethasone treated group showed significant reduction in total protein level and globulin level. Results of serum albumin level were non-significant. Most important of all is serum A/G ratio which showed significant results. Significant reduction in serum A/G ratio in dexa treated group in comparison to untreated group thus dexamethasone was nephro-protective.